Leadership and Speech Acts of Maulanasyaikh: Character and Educational Values in The Younger Generation - Siti Ainun Hasanah; Bambang Eka Saputra; Lalu Murdi Murdi; Hary Murcahyanto (IJE : Interdisciplinary Journal of Education, 2023)
This study aims to examine Maulanasyaikh's daily speech acts, including when giving recitations, interacting with the community, and family, in politics and government, and other speech acts that have character values for the younger generation. In addition, this study also aims to understand the values contained in Maulanasyaikh's speech acts. This research was conducted in the village of Pancor Bermi Village, Selong District, East Lombok Regency, West Nusa Tenggara, four months from March to June 2022. Using a qualitative approach with the historical method, this research focuses on the value of speech acts of TGKH Muhammad Zainuddin Abdul Madjid (Maulanasyaikh). This approach allows data collection from in-depth written or oral words. The historical method involves the steps of heuristics, criticism, interpretation, and historiography. The results of this study reveal Maulanasyaikh's speech acts in various contexts, including interacting with students, in the social sphere, towards the congregation, in politics, and towards his family. Maulanasyaikh demonstrated politeness, caring, and teaching moral and ethical values in his communication and actions in various aspects of his life.